Vitamin D deficiency and the COVID-19 pandemic. (September 2020) - Zemb, Patrick; Bergman, Peter; Camargo, Carlos A.; Cavalier, Etienne; Cormier, Catherine; Courbebaisse, Marie; Hollis, Bruce; Joulia, Fabrice; Minisola, Salvatore; Pilz, Stefan; Pludowski, Pawel; Schmitt, François; et al.
Highlights: Vitamin D deficiency is very common. Randomised controlled trials showed that vitamin D decreases acute respiratory infections (ARIs). Vitamin D deficiency is an easily modifiable factor of ARIs. Daily vitamin D supplementation with moderate doses is safe and cheap. Even a small decrease in COVID-19 infections would easily justify this intervention.